Influence of co-milling oxide physical properties on the structural changes of natural clinoptilolite zeolites - Natsagdorj, Narantsogt; Lkhagvasuren, Narangarav; Munkhjargal, Bolortuya; Temuujin, Jadambaa (Mongolian Journal of Chemistry, 2023)
Zeolites are a family of open-framework aluminosilicate minerals used in many diverse fields, including building materials, agriculture, water treatment, and catalysis. In this study, natural zeolites were mechano-chemically treated by co-milling with corundum and cristobalite. The idea behind the study was that co-milling with high-hardness oxides would cause natural zeolite to undergo more structural distortion, potentially increasing its reactivity and sorption capabilities. Corundum has a density of 3.95 g/cm3 and a hardness of 9, while cristobalite has a density of 2.27 g/cm3 and a hardness of 6-7, according to the Mohs hardness scale. In a planetary ball mill, the zeolites and 20 wt.% of various oxides were co-ground for 30 min. The grinding media used were hardened steel balls with a weight ratio of 20:1 between the balls and the minerals. Raw minerals and milled products were evaluated using X-ray diffraction, Fourier-transform infrared spectroscopy and scanning electron microscopy. It revealed that co-milling with different hardness oxides had a minor effect on the structural distortion of raw zeolite. Crystallite size reduction and amorphization were observed in high hardness oxides rather than in zeolite particles. After milling, the amorphization of natural zeolite milled alone was 30.4%, while no significant amorphization was observed when co-milled with corundum and cristobalite. Preliminary results of Cr(VI) adsorption tests on raw and milled zeolites indicate that co-milling with high-hardness oxides is not the preferred method to enhance the activity of natural zeolite.